Oprah, Celebrity and Formations of Self - Wilson, S. author. aut Link
X, 230 p.
Keywords: Oprah Winfrey has transcended her status as talk show host to become a cultural icon of some considerable stature. This book explores the nature of Oprah's celebrity persona and considers the relevance that she has to contemporary audiences. The stories recounted by guests, and the ways in which confessional discourse works to produce a particular relationship between Oprah, her guests and the audience members are considered within the context of contemporary American culture.